Profesores integrales que forman y evalúan en ciencias por competencias (2017)
A proposal is presented that entails a reflection, theorization and methodological construction of the importance of the competencies in teaching, learning and assessment as a formative process. With a team made by faculty directors and a professor representing each of them, a process was carried out where, in addition to a theoretical approach to competency-based assessment in the teaching and learning of sciences, which is closely linked to the subjects’ curricula, progress has been made in a methodological construction that brings together the professors from the School of Sciences of Universidad Antonio Nariño (UAN) in a continued effort to strengthen their work through surveys, documents and workshops aimed at generating specific products. Among the results of a seminar-workshop, the conclusions of which aim to continue with the identification of aspects to be improved in the teaching practice, we highlight the creation of a bank of questions that follow a series of methodological guidelines associated with the competencies to be evaluated and the critical review of subject curricula grouped by fields of knowledge.